Pengaruh Struktur Modal, Modal Intelektual, dan Tax Avoidance terhadap Nilai Perusahaan - Maria Paschalia Apriliani; Ni Putu Budiadnyani (Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This study aims to analyze the effect of capital structure, intellectual capital, and tax avoidance on firm value in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2024 period. The research is motivated by the strategic role of firm value as a signal of performance and long-term prospects amid economic dynamics, shifting consumer behavior, and post-pandemic policy pressures. A quantitative approach is employed using purposive sampling, resulting in 36 sample companies and 144 firm-year observations based on annual financial reports. Data are analyzed using multiple linear regression with SPSS, preceded by classical assumption tests including normality, multicollinearity, heteroskedasticity, and autocorrelation. The results show that capital structure has a positive and significant effect on firm value, supporting signaling theory which argues that sound financing decisions convey positive information to investors. Intellectual capital has a negative and insignificant effect on firm value, indicating that intellectual assets have not yet been optimally managed or fully appreciated by the market in this sector. Tax avoidance has a positive and significant effect on firm value, consistent with agency theory, suggesting that legally and prudently managed tax avoidance can improve tax efficiency, enhance profitability, and strengthen investor perceptions. Simultaneously, capital structure, intellectual capital, and tax avoidance significantly influence firm value, underscoring the importance of financial structure, intangible resources, and tax strategies in enhancing competitiveness and firm value in the food and beverage industry.